Dimensionamento e instalação de um sistema solar fotovoltaico em um veículo aéreo não tripulado (VANT) do tipo multirotor alimentado somente por energia fotovoltaica - Velandia, William Felipe Orjuela (2018)
Currently, the search for new alternatives and clean technologies of fuels that allow to mitigate the environmental impact caused by the conventional energies, has become a wide field of study in engineering level in search of the energetic sustainability. Given that the sun is a renewable source of energy, and every day, its potential increases due to major advances, development of new technologies, reduction of production costs and increased efficiency of solar energy capture systems. Therefore, it was decided to establish as a project objective to use this type of energy, and by means of a photovoltaic arrangement and couple it in a multirotor type unmanned aerial vehicle system. In this study, a system was designed so as to feed only by solar energy, leaving aside the use of batteries or other types of energy supply. For the development of the present research, three types of multirotors were constructed, so that in the construction process, the successor of each of them, had improvements in design. For each of these prototypes, a photovoltaic array is designed to allow the capture of solar radiation and converts it into electrical energy to feed them. Solar radiation data were collected during one week, with the help of a pyranometer located in the solar energy and natural gas laboratory of the Federal University of Ceará. From these data, an analysis of the appropriate time interval to perform the tests of energy supply, to observe the behavior of the prototype to be irradiated directly by the sun, besides recording the data in detail of the variation of current and tension. After testing, it has been shown that it is possible to power an unmanned aerial vehicle of the multirotor type by means of solar energy. The study showed that for the prototype to take off from de ground, the total weight of each of its components, must be taken into consideration. In addition, according to the data obtained, drone 3.0 managed to reach a maximum power of 141.57 W, and it was demonstrated by the pyranometer that the ideal time of higher radiation occurs in the interval of 11 to 13 hours